Problemy edukacyjnego wspierania potrzeb innowacyjnych województwa podkarpackiego - Łunarski, Jerzy; Stadnicka, Dorota (Problems of Educational Support of Innovational Needs in Podkarpacie Province, 2006)
The paper shows the chosen results of the research, which were made in connection with preparing regional innovational strategy. The results show that the society is not prepared enough to create innovations. It is about their poor knowledge, no connection with R&D organizations and lack of money. In the paper the problems with education are discussed. And the designing process of the new study program, which considers market requirements, is suggested.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 515-522